Obese children without comorbidities have impaired microvascular endothelial function. (17th January 2014) - Hedvall Kallerman, P; Hagman, E; Edstedt Bonamy, A‐K; Zemack, H; Marcus, C; Norman, M; Westerståhl, M
Abstract Aim The aim was to test acetylcholine‐induced endothelium‐dependent vasodilatation in obese children without comorbidities, compared with normal weight controls, and to analyse associations between vasodilatation and other potential risk factors. Methods Endothelium‐dependent vasodilatation was induced by transdermal iontophoresis of acetylcholine in 54 obese children (8.3–18.2 years old, 41% girls) and 44 normal weight controls (7.5–20.2 years old, 82% girls), and the subsequent change in perfusion was measured with laser Doppler flowmetry. In a subgroup of the obese children, associations between acetylcholine‐induced vasodilatation and blood lipids, glucose/insulin metabolism, inflammation, 24‐h ambulatory blood pressure (ABP), cardiovascular fitness and duration of obesity were evaluated. Results We found a lower endothelium‐dependent vasodilatory response to acetylcholine in the obese children than the controls (p < 0.001). The peak perfusion response was 33% lower in obese children (p = 0.001). There was a trend towards lower vasodilatation in obese children with higher levels of triglycerides (p = 0.07). Children with the shortest duration of obesity exhibited the lowest vasodilatation (p = 0.03). No associations were found between 24‐h ABP, cardiovascular fitness, inflammation and glucose/insulin metabolism. Conclusion Obese children without comorbidities have significantly impaired microvascular endothelial function. The children who had been obese for a longer time seemed less affected.